Proposed Business Strategy to Improve Sales of Jackob Polish Bandung - Timothy Winata, Hansen; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2016)
Abstract— Growth of the automotive industry is like the never ending process. Everyday in the world each automotive factory produce many cars in each type. A car consists of so many parts and as time goes by the parts need to renew again. There are parts when it broke or already reach the time replacement then that parts must be replace with a new one. There are some chance in parts of car body to open the business. In fact that the car user is increasing day to day. Based on that situation then Jackob Polish Bandung see the opportunity to grab the market in automotive aspect especially in headlamp cleaning. Jackob Polish Bandung focus in headlamp service which is include cleaning and custom blackhousing and need to achieve the target in order to get revenue. There is a need on marketing and promotion support to achieve the target. Jackob Polish Bandung challenged to increase sales on each month so they can reach the long term target. The analysis include the internal and external aspects of the Jackob Polish Bandung. In the internal analysis was done by using Value Chain analysis, resources analysis and VRIO analysis. And the external analysis was done by using PEST analysis and Porter’s 5 Forces analysis. The results of internal and external analysis will be used to proposed the strategies and also TOWS matrix. The proposed strategies must be implemented in order to show the different before action plans done and after action plan done. These strategies also will be guidance for Jackob Polish Bandung for taking the decision. The implementation plans is done by using financial projections performance until 2020 and action plans with person in charge within. Keywords: business strategy, automotive industry, TOWS matrix